Phenotype of human T helper and suppressor cells in an in vitro specific antibody response. - Callard, R; Smith, C; Beverley, P (1982)
Monoclonal anti-human T cell antibodies have been used to identify cells which provide help for an in vitro specific antibody response to influenza virus and also those which suppress the response of allogeneic peripheral blood mononuclear cells. The helper cells carry antigens defined by the Leu 3a and OKT4-antisera, whereas the suppressor cells are predominantly Leu 2a- and OKT8-positive. Help and suppression in this secondary in vitro antibody response are therefore provided by antigenically distinct T cell subsets.